2017
DOI: 10.1186/s12870-017-1083-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volatile compounds produced by Ralstonia solanacearum on plant growth promoting and systemic resistance inducing potential of Bacillus volatiles

Abstract: Background: Microbial volatiles play an expedient role in the agricultural ecological system by enhancing plant growth and inducing systemic resistance against plant pathogens, without causing hazardous effects on the environment. To explore the effects of VOCs of Ralstonia solanacearum TBBS1 (Rs) on tobacco plant growth and on plant growth promoting efficiency of VOCs produced by Bacillus subtilis SYST2, experiments were conducted both in vitro and in planta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 48 publications
4
60
0
Order By: Relevance
“…Bacillus VOCs are known not only to promote plant growth, but also to provoke ISR against plant pathogens in plants (Tahir et al, 2017b). The VOCs synthesized by B. subtilis SYST2 enhance ISR in tobacco plants against wilt pathogen Rhizoctonia solani (Tahir et al, 2017c). Recently, it has been reported that acetoin and 2,3 butanediol, VOCs produced by FZB42, could induce stomata closure in plant leaves, which prevents invading of foliar pathogens (Wu et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus VOCs are known not only to promote plant growth, but also to provoke ISR against plant pathogens in plants (Tahir et al, 2017b). The VOCs synthesized by B. subtilis SYST2 enhance ISR in tobacco plants against wilt pathogen Rhizoctonia solani (Tahir et al, 2017c). Recently, it has been reported that acetoin and 2,3 butanediol, VOCs produced by FZB42, could induce stomata closure in plant leaves, which prevents invading of foliar pathogens (Wu et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolites are various, such as phenazines (Burkhead et al, 1994), iturin A (Ahimou et al, 2000), bacillomycin (Volpon et al, 1999), polymyxin (Kagan et al, 1951;Cruz et al, 2007;Niu et al, 2013), and fusaricidin (Vater et al, 2016). Inducing resistance in plants is another important indirect growth-promoting mechanism of PGPR (Tahir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SJ Volatile compounds Rhizoctonia solani , Phytophthora nicotianae Tobacco Kim et al ( 2015 ) Bacillus fortis IAGS 162 Phenylacetic acid Fusarium oxysporum f.sp. lycopersici Tomato Akram et al ( 2016 ) Bacillus subtilis DZSY21 Lipopeptides Bipolaris maydis Maize Ding et al ( 2017 ) Pseudomonas aeruginosa PM12 3-Hydroxy-5-methoxy benzene methanol (HMB) Fusarium oxysporum Tomato Fatima and Anjum ( 2017 ) Bacillus subtilis SYST2 Albuterol, 1,3-propanediol Ralstonia solanacearum TBBS1 Tobacco Tahir et al ( 2017 ) Pseudomonas protegens CHAO Orfamide A Cochlibolus miyabeanus Rice Ma et al ( 2017 ) Bacillus amyloliquefaciens (UCMB5113) Fengycins Alternaria brassicicola Arabidopsis thaliana Asari et al ( 2017 ) Saccharothrix yanglingensis (Hhs.015) BAR11 protein Pseudomonas syringae pv. tomato DC3000 Arabidopsis thaliana Zhang et al ( 2018 ) Bacillus amyloliquefaciens , Bacillus subtilis Iturin A, Fengycin, Bacillomycin Fusarium moniliforme Maize Gond et al ( 2015 ) …”
Section: Microbial Induction Of Systemic Resistance In Plant To Biotimentioning
confidence: 99%
“…Also implicated in the protection of plant against pathogen is the volatile organic compounds produced by beneficial rhizomicrobes (Table 2 ) which performs their role by the initiation of systemic resistance in the plants. Volatile organic compounds are gaseous, low molecular weight organic compounds such as albuterol, 1,3-propanediol (Tahir et al 2017 ), 3-pentanol, and 2-butanone (Song and Ryu 2013 ) which can activate the plant immune system and imped pathogenic microbes from a distance. For this type of compound, distance is never a barrier to its action compared with other chemical substances of higher molecular weight like exopolysaccharide and proteins that are involved in pathogen control which acts only in close proximity/contact with the plant (Yunus et al 2016; Xie et al 2014; Raza et al 2016 ).…”
Section: Elicitors In the Induction Of Systemic Resistance To Biotic mentioning
confidence: 99%